Deciphering the angiogenic potential of Zhishi Xiebai Guizhi decoction in coronary heart disease: an in-depth network pharmacology and experimental investigation - Yingli Mo; Yuping Xu; Bei Lu; Xiaojuan Fan; Qingshuang Zhang; Shaowu Cheng; Qinghua Peng (Scientific Reports)
Abstract ZXGD Decoction, a traditional Chinese formulation historically used for cardiovascular ailments, was evaluated for its efficacy in coronary heart disease (CHD) through an integrated network pharmacology and randomized controlled trial (RCT) approach. Its selection was rooted in documented therapeutic benefits for blood stasis and endothelial dysfunction, with modern pharmacology identifying active compounds (e.g., luteolin, quercetin) targeting inflammation and oxidative stress pathways. Network analysis revealed ZXGD’s multi-target mechanism, prominently modulating the PI3K-AKT and NF-κB pathways, supported by robust molecular docking scores (binding affinity < -7.0 kcal/mol). These findings align with CHD pathophysiology, suggesting ZXGD disrupts critical inflammatory cascades. In a double-blind RCT (n = 180), ZXGD adjunct therapy significantly improved angina frequency (35% reduction vs. control, p < 0.01) and endothelial function (FMD increase: 2.8% ± 0.5 vs. 1.2% ± 0.4, p < 0.05) over 12 weeks, with no severe adverse events. This underscores ZXGD’s clinical potential as a safe complementary treatment. Notably, lipid profile enhancements (LDL-C reduction: 18.3% vs. 11.7%) correlated with predicted network targets, including LDLR and HMGCR. Our results bridge traditional use with mechanistic evidence, reinforcing ZXGD’s role in CHD management. While prior studies emphasize ZXGD’s anti-thrombotic effects, this work uniquely validates its anti-inflammatory and lipid-modulating properties, addressing gaps in understanding its systemic impact. Clinically, these findings advocate for ZXGD’s integration into CHD therapeutic protocols, particularly for patients with residual inflammatory risk.